Exploring Diversity in Neolithic Agropastoral Management in Mainland Greece Using Stable Isotope Analysis. (4th March 2023) - Vaiglova, Petra; Coleman, John; Diffey, Charlotte; Tzevelekidi, Vasiliki; Fillios, Melanie; Pappa, Maria; Halstead, Paul; Valamoti, Soultana Maria; Cavanagh, William; Renard, Josette; Buckley, Michael; Bogaard, Amy
ABSTRACT: New stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope values of charred plant and bone collagen remains from 6th mill. BCE Halai, central Greece, together with datasets from 6th mill. BCE Kouphovouno, southern Greece, and later 6th/early 5th mill. BCE Makriyalos, northern Greece, demonstrate how early farming communities in mainland Greece adapted mixed farming strategies to distinct local environmental and cultural settings. Intra-site similarities and differences in δ 13 C and δ 15 N values of distinct crop species, along with the intra-species variabilities in stable isotopic values, are used to assess the cultivation choices that farmers at the three sites made to fulfil distinct economic goals. At Halai, farmers cultivated multiple crops under variable soil conditions, a strategy likely geared towards minimising overall risk in a relatively arid coastal setting. At better-watered Kouphovouno, by contrast, farmers practiced strategic manuring to maximise the yield of free-threshing wheat, likely grown exclusively for human consumption and rotated with nitrogen-fixing pulses. At Makriyalos, the limited sample size of cereal remains suggests a lack of intensive manuring, in contrast to the two other sites. Assessment of which crops may have been consumed by livestock sheds further light on symbiotic relationships between crop cultivation and animal husbandry.